Springdale, Leavenworth County - Baker, Zach (Kansas State University, The Chapman Center for Rural Studies, 2010)
The author describes the life of an early Irish Catholic settlement in eastern Kansas. Originally a Quaker community, Irish immigration "exploded" there just after the Civil War, eventually stamping the town with a particular religious culture. After railroads made the Fort Riley mail road obsolete, Springdale declined. St. Thomas Catholic Church was a vital center for decades.
Baker, Zach, “Springdale, Leavenworth County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/3.
Keywords: Springdale; Leavenworth County; St. Thomas Catholic Church; Irish Catholics; Quakers; Zach Baker